Analysis of Strategic Plans and Innovations to Accelerate Economic Sector Recovery (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
Recovery of the economic sector is a top priority in facing global economic challenges that continue to grow. This research aims to analyze strategic plans and innovations that can be implemented to accelerate the economic sector recovery process. The analysis results show that integration of information technology, sustainable infrastructure development, and increasing human resource capacity are key elements in the economic recovery plan. Risk-based strategies and adaptation to rapid technological developments were also found to play an important role in ensuring the sustainability of economic recovery.